Comparative Analgesia Between Acupuncture and Dipyrone in Odontalgia - Talita B. de Almeida; Vera L.R. Zotelli; Ronaldo S. Wada; Maria L.R. Sousa (Medical Association of Pharmacopuncture Institute, 2019)
The aim of this study was to assess whether the effectiveness of acupuncture is similar to the use of analgesics in the management of toothache. The research included 56 volunteers who were divided into 4 groups: Real Acupuncture group, Placebo Acupuncture group, Real Dipyrone group, and Placebo Dipyrone group. The interventions of the study were performed before the dental care. Inclusion criteria were toothache of pulpal origin with pain scale (Visual Analogue Scale) above 4, absence of medication for the pain, and aged over 18 years. The Real Acupuncture volunteers received a session of acupuncture using piercing needles, while volunteers from the Placebo Acupuncture group received an acupuncture session using non-piercing sham needles. Volunteers from the Real Dipyrone group received a dipyrone tablet and the Placebo Acupuncture group received a tablet with no active ingredient. Before any therapeutic intervention, we collected samples from the volunteers' saliva to analyze the salivary cortisol, the volunteers rated the intensity of their pain using VAS, and we measured their energy level by the Ryodoraku method. After 20 minutes of treatment, all the volunteers' analysis parameters were collected again. The Real Acupuncture group presented a greater reduction of VAS than the reduction obtained by the Real Dipyrone group (p<0.05). There was no statistically significant difference between the groups for the salivary cortisol and energy level variables. It can be concluded that acupuncture was more effective in reducing odontalgia than the dipyrone and that it can be an alternative for odontalgia management. Keywords: acupuncture therapy, dipyrone, hydrocortisone, pulpitis